An Investigation of the Correlation Between Il-8, Il-10 and Nutritional Proteins in Patients with Sleep Disorders in Chronic Obstructive Pulmonary Disease - Liang, Mei; Zhou, Mei; Fu, Xiaofeng; Zhou, Qianyun; Li, Liang (Journal of Medical Biochemistry, 2025)
Introduction: Chronic obstructive pulmonary disease (COPD) is one of the most common respiratory diseases worldwide, with an increasing incidence in recent years. In this study, we analyzed the relationship between Interleukin-8 (IL-8), Interleukin-10 and COPD to provide reference for clinical diagnosis and treatment in the future. Material and methods: A randomized controlled trial was conducted on 56 COPD patients and 56 concurrent healthy volunteers who visited our hospital from March 2022 to December 2022. Among them, COPD patients served as the research group and healthy volunteers served as the control group. To compare the IL-8 and IL-10 of the two groups and to analyze the relationship between IL-8, IL-10 and lung function, nutrient proteins, clinical efficacy and prognosis of the research group. Results: IL-8 was higher in the study group than in the control group, and was negatively correlated with lung function indices and nutrient proteins (P<0.05). IL-10 in the research group was lower than that in the control group, and there was a positive correlation with lung function indexes and nutritional proteins (P<0.05). After treatment, IL-8 was lower and IL-10 was higher in the research group (P<0.05). In addition, IL-8 and IL-10 in the research group demonstrated excellent assessment of COPD occurrence, sleep disturbance, and prognostic recurrence. Conclusion: IL-8, IL-10 not only directly participate in the occurrence of COPD by affecting the human immune microcirculation, but also accelerate the progression of COPD by causing malnutrition.